In memory of her majesty Queen Elizabeth II [videorecording (DVD)] - Raworth, Sophie, 1968-; Bruce, Fiona, 1964-; Lester, Adrian; Young, Kirsty (BBC, 2023)
Through four extraordinary documentaries, we follow some of Queen Elizabeth II's most defining moments, from her unique coronation to her sympathetic and inspiring speeches. With singular access and painstaking detail, we see how her legend was crafted, and take a peek behind the curtain to get a sense of the woman who was Queen.